HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KEPERCAYAAN DIRI PADA REMAJA - Rahmah " Desi; Jumaini " "; Sri " Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The purpose of this research was to determine the relationship family support with confidence level of adolescents. The method of this research was descriptive correlation with cross sectional approach. This research was held in MAN 2 Model Pekanbaru with 194 respondents that taken use simple random sampling. This research used a questionnaire as a measuring tool that has been tested for validity and reliability. This research using univariate analysis to knew frequency distribution and bivariate analysis using Chi- square test. The results showed that the majority of respondents are male totaled 104 respondents (53,6%), the majority of respondents in young middle age (15-17 years of age) of 190 respondents (97,9%), most majors who are majoring Natural Sciences amounted to 115 respondents (59,3%). Respondents who had positive family support totaling 101 respondents (52,1%). Respondents who have a high confidence as much as 104 respondents (53,6%). Bivariat analysis using Chi-square test was obtained p value 0,000 < 0,05, it means there is a relationship family support with a confidence level of adolescents. Family can give more support for adolescents with two-way communication method and encourage adolescents to do the positive activities that can increase of adolescents. Keyword: Adolescents, confidence, family support.